Leveraging Data Science in Predicting and Preventing Child Health Issues - Jack Harrison Scott; Oliver Henry Carter (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Data science and analytics are revolutionizing healthcare by providing insights into disease prevention and early intervention. This paper investigates the use of data science in predicting and preventing child health issues, such as respiratory diseases, allergies, and infectious diseases. By analyzing large datasets from healthcare providers and tracking environmental factors, the paper demonstrates how data science can predict health trends, identify risk factors, and inform public health policies for children.